OPTIMIZATION OF CONDITIONS FOR THE PRODUCTION OF GLUCOAMYLASE FROM ASPERGILLUS FUMIGATUS: PURIFICATION AND KINETIC STUDIES OF GLUCOAMYLASE - M.Tayyab; H.Ali; B.Muneer; S.Firyal; A. R.Awan; M.Wasim; F.Masood; S.Saeed (Journal of Animal and Plant Sciences, 2019)
Filamentous fungi is the basic source of hydrolytic enzymes and widely used for industrial applications. Aspergillus fumigatus have been widely used for the production of hydrolytic enzymes. The present study was undertaken to demonstrate the production of glucoamylase from Aspergillus fumigatus using wheat bran as substrate. A. fumigatus was isolated from organic waste samples from river Ravi, Lahore, Punjab, Pakistan and the conditions were optimized for its growth. Various carbon and nitrogen sources were utilized for the supplementation of growth medium in order to produce higher level of glucoamylase. The produced enzyme was partially purified by fractional ammonium sulphate precipitation followed by dialysis for the removal of salt. The dialyzed sample was further purified by ion exchange and gel filtration chromatography. The purified protein was utilized for the kinetic studies. Purification studies resulted in 12 fold purification with 45% yield of the glucoamylase. SDS-PAGE analysis of the purified enzyme revealed an approximate size of 60 kDa. Under optimal conditions, we were able to produce 28 U/mL of glucoamylase. Highest enzyme activity was observed when A. fumigatus was grown on 3% wheat bran in the presence of 0.7% Tween-80 at 40oC for 72 hours at pH 5.0. Kinetic studies demonstrated the Km and Vmax values 9.1 mg/mL and 40 µM min-1 mg-1 respectively when starch was utilized as substrate. Present study revealed a new source of glucoamylase, which have ability to utilize a variety of agriculture products as carbon sources that can be useful for enzyme industry. This study discovered a new strain, which is a unique machine that can act as an attractive alternative source for the production of industrial enzymes for starch hydrolysis. To our knowledge this is the highest glucoamylase activity from Aspergillus fumigatus sp. so far.
Keywords: Glucoamylase; Aspergillus fumigatus; wheat bran; optimization